2018
DOI: 10.1016/j.cell.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Origins of Neural Substrates for Land Walking

Abstract: Walking is the predominant locomotor behavior expressed by land-dwelling vertebrates, but it is unknown when the neural circuits that are essential for limb control first appeared. Certain fish species display walking-like behaviors, raising the possibility that the underlying circuitry originated in primitive marine vertebrates. We show that the neural substrates of bipedalism are present in the little skate Leucoraja erinacea, whose common ancestor with tetrapods existed ∼420 million years ago. Leucoraja exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 56 publications
10
101
0
Order By: Relevance
“…A previous study reported that the localization of LMC neurons expands posteriorly in the neural tube of skates (24). However, the peripheral innervation pattern of batoid spinal nerves during embryogenesis has not been studied in detail.…”
Section: Branching Of Spinal Nerves Into the Body Wall And Pectoral Finsmentioning
confidence: 96%
See 3 more Smart Citations
“…A previous study reported that the localization of LMC neurons expands posteriorly in the neural tube of skates (24). However, the peripheral innervation pattern of batoid spinal nerves during embryogenesis has not been studied in detail.…”
Section: Branching Of Spinal Nerves Into the Body Wall And Pectoral Finsmentioning
confidence: 96%
“…Loss of the HoxC cluster results in high FoxP1 expression, and the through development of the LMC between brachial and lumbar domains in skates (24). Unexpectedly, a previous study identified a minor population of MNs that is similar to the HMC at pectoral and pelvic domains with LMC in the neural tube of skates (24), implying that skates retain unique patterns of innervation at the brachial level compared with other finned vertebrates. However, developmental patterns of peripheral nerves in skates and other rays have not yet been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In situ hybridization of tissue sections was performed as previously described using DIG labeled probes 48 .…”
Section: In Situ Hybridizationmentioning
confidence: 99%